Sports Development Index as a Reflection of Disparities and Challenges in Sports Sector Equity - Saparia, Andi; Humaedi, Humaedi; Abduh, Ikhwan (Universitas Pendidikan Ganesha, 2025)
Ideal sports development is characterized by equal distribution of quality and access to sports across all regions. However, sports development in several regions still shows significant disparities. This study aims to analyze the Sports Development Index (SDI) in depth by synthesizing the values ​​of the dimensions of sports development to provide an objective picture of the condition and disparities in sports development. This study is an observational study with a quantitative descriptive design. The research subjects were the general public, sports practitioners, and government officials selected using a multistage random sampling technique, with 30 respondents. Data were collected through questionnaires, interviews, documentation, and physical fitness tests, using questionnaires and interview sheets as instruments. Data analysis was carried out by calculating the average SDI value for each region and comparing it with national norms. The results show that the three regions studied are in the low category. Each region has relative advantages in different dimensions, but not yet strong enough to improve the overall SDI classification. The conclusion of this study indicates that sports development in the Pasigala region is not evenly distributed and still requires more focused policy intervention. This research provides important implications for regional government strategic planning in accelerating equity and improving the quality of sustainable sports development.